Pelatihan Pembukuan Pengusaha UMKM Perdagangan Ban : Bookkeeping Training for UMKM Tire Trading Entrepreneurs - Irawan, Candra (Edujavare Publishing, 2025)
MSMEs in the tire trading sector play an important role in the local automotive industry, but often face obstacles in preparing accurate financial reports due to limited accounting knowledge. This causes difficulties in monitoring cash flow, measuring profitability, and accessing funding sources. Therefore, this community service aims to improve the understanding and skills of MSME actors in preparing simple financial reports through bookkeeping training. The method used is Participation Action Research (PAR) with a participatory approach involving lectures, interactive discussions, and direct assistance. This training includes material on the importance of financial reports, how to record daily transactions, and the preparation of balance sheets and profit and loss statements. The results of the community service show that participants experienced an increase in understanding in recording transactions systematically and structured, were able to separate personal and business finances, and prepare more accurate simple financial reports. However, there are still some weaknesses such as limited mentoring time and low understanding of accounting terms. In conclusion, this training is effective in improving the financial literacy of MSME tire trading actors, but more intensive mentoring and utilization of financial recording technology are needed to achieve more optimal results.